Affective surfing in the visualized interface of a digital library for children. Issue 4 (July 2015) - Wu, Ko-Chiu
Highlights Elucidation of children's info-seeking behaviors using virtual retrieval interfaces. The use of SEM to explore the relationship between fun and uncertainty. Children prefer a virtual retrieval interface when at play. Text/sound channels are less definite but easier to use than icon channels. Children at play are willing to endure a high degree of uncertainty/control.